Factors influencing withdrawal behavior of Malaysian Islamic bank customers: empirical evidence from three major issues - Abduh, Muhamad (2013)
As interest is prohibited, the reliance of Islamic banking towards deposits from depositors is higher than conventional banking. This study is aimed at investigating individual factors that may influence the withdrawal behavior of Malaysian Islamic banks customers. The withdrawal behavior studied here is in conjunction with three major issues which are (i) issues of non-shariah compliance, (ii) lower returns as compared to other banks, and (iii) rumors of a financial crisis that may affect the bank in the near future. The research employed a direct survey through a self-administered questionnaire handed out to Islamic banks customers in Malaysia using the multi-stage sampling technique. Afterwards, the logit-regression model is used to classify the depositors based on the probability of them withdrawing from Islamic banks due to those issues. The intention to avoid banking interest, type of account, working status, bank status, and bank ownership are the significant factors that could influence withdrawal behavior due to violation of shariah principles by the bank. Working status and bank ownership are the factors which influence withdrawal behavior due to lower return. Lastly, for the issue of banking crisis, factors emerged to be significant are type of account, total deposit in bank, awareness on deposit insurance, intention to avoid banking interest and perception that Islamic banks are less affected by the banking crisis.